Increase of Fibroblast Cells in Wound Healing of Diabetes Mellitus Male Rats (Rattus Norvegicus) Using Aloin - Vani, Ade Teti; Arlita, Cindy; Lismawati, Lismawati; Dewi, Nadia Purnama; Abdullah, Dessy; Oktora, Meta Zuliyanti (Oshada, 2024)
The healing process wound on the skin diabetic experience slowdown because dysfunction fibroblasts. Aloins boost expression fibroblasts that can accelerating the process of wound healing in patients with Diabetes Mellitus (DM). Objective study that is for now effect enhancement cell fibroblasts in wound healing wound I t mouse male DM with aloe giving. Method study use principle true experimental with approach post-test serial only control group design. Treatment form wound cut on mice. Group study using 4 groups with a negative control in the form mouse healthy, positive control form DM mouse. group action 1 in the form of DM rats were given 1.25 mg/ kg BW aloin and treatment 2 was in the form of DM rats given 2.5 mg/ kg BW aloin. Expression fibroblasts calculated on day 7 and day 14. Analysis bivariate using the Friedman test continued with the Wilcoxon Post- Hoc test. Research results that are there is enhancement fibroblasts significant in the group treatment given with aloein a dose of 1.25 mg/ kg and a dose of 2.5 mg/ kg. The conclusion is that Aloin accelerates wound healing wound incision in DM rats with mechanism enhancement expression fibroblasts with minimum dose of 1.25 mg/ KgBB. Research suggestions that is examination of re- epithelialization and density Dermal collagen in wound healing wound I t DM rats given aloein in the study next.